Enabling Transgenic Plant Cell–Derived Biomedicines with Nanotechnology. Issue 1 (24th November 2020) - Chiu, Yee Ting Elaine; Choi, Chung Hang Jonathan
Abstract : Transgenic plants are promising factories for manufacturing pharmaceutical small molecules or proteins safe for human consumption. Eukaryotic plant cells can synthesize proteins with precise posttranslational modifications, but microbes cannot. Conventional transformation methods (e.g., electroporation, Agrobacterium ‐mediated transformation, and biolistic particle delivery) often suffer from inefficient transformation, damage to plant tissues and cells, or applicability to a narrow range of plant species. Notably, the cell wall poses a physical barrier that obstructs effective delivery of nucleic acids to plant cells. Nanoparticles (NPs) are emerging carriers of nucleic acids to plants because they are sufficiently small to diffuse through the cell wall, enter plant cells without the aid of external forces, and inflict limited damage to the plant cells in a broad variety of plants. Herein, three areas of the phytonanotechnology field that merit comprehensive investigations are outlined, namely, the design considerations of NPs for gene delivery to plant cells, homing of NPs to specific organelles (e.g., nucleus and chloroplast), and transformation of plant suspension cells. This perspective concludes with recent insights into scale‐up production of therapeutics by using bioreactors. NPs are poised to catalyze the transformation of plant cells for producing therapeutics in bioreactors at reduced costs, high purity, and improved scale. Abstract : Nanoparticles, as emerging gene carriers to plant cells, can catalyze the application of transgenic plants for manufacturing pharmaceuticals. Herein, the design considerations of nanoparticles for gene delivery to plant cells and specific organelles are outlined. Development of nanoparticle‐based methods for transforming plant suspension cells aids the production of pharmaceuticals in bioreactors at reduced costs, high purity, and improved scale.